Inside Cover: Mesoporous Gallosilicate with 3 D Architecture as a Robust Energy‐Efficient Heterogeneous Catalyst for Diphenylmethane Production (ChemCatChem 7/2013). Issue 7 (25th June 2013) - Anand, Chokkalingam; Joseph, Stalin; Lawrence, Geoffrey; Dhawale, Dattatray S.; Wahab, Md. Abdul; Choy, Jin‐Ho; Vinu, Ajayan
<x xml:space="preserve">Abstract</x> Green catalytic boat The cover picture shows the eco‐friendly synthesis of diphenylmethane by using a gallosilicate with a 3 D porous structure. In their Full Paper on p. 1863 ff., C. Anand, A. Vinu et al. demonstrate the role of gallium in the KIT‐6 molecular sieves on the Friedel–Crafts alkylation of aromatics. The prepared highly stable and recyclable catalyst shows a high activity even at reaction temperatures as low as 313 K with a high benzylchloride conversion and diphenylmethane selectivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>